Enhancing nutrition program benefit utilization through targeted intervention strategies. - Potvin, Rebecca (My University, 2025)
This report provides an in-depth review of my Applied Practice Experience (APE). This time was spent with the Women, Infants, and Children Program (WIC) at the Riley County Health Department in Manhattan, Kansas. WIC is a national public health nutrition program designed to improve nutrition and food security for some of the most vulnerable populations. This includes early intervention focused on pregnant individuals, the resulting infants, and children up to the age of five. The program is also income-based, meaning to qualify, household income must be at or below 185% of the Federal Poverty Guidelines. A focus on nutrition makes WIC unique from other food-based programs. Items must meet specific USDA guidelines to be allowed to be purchased using WIC benefits. Therefore, only particular food items are considered “WIC Approved.” While this format helps guide food choices with nutrition in mind, it does make purchasing at local grocery stores more complex to meet the requirements. This can lead to client frustrations and potentially less-than-optimal benefit purchasing habits. While working with my preceptor, information about potentially accessible data about the local office was recently confirmed. My preceptor was very interested and open to finding out what information could be gathered and how it could be utilized. Our focus began with redemption percentages and realizing that many participants weren’t using their full benefits. An idea was formed to create an intervention which could improve utilization. Ideally, this would help meet the ideals of the WIC program: decrease food insecurity, improve health outcomes, and sustain demand for the program. From this, I created a logic model evaluating what resources, activities, and outcomes could be possible with the project, which was used to refine the focus of the intervention. Based on preliminary data, I was able to evaluate which benefit categories were least redeemed and which households used little to no assigned benefits. This information was then shared with local staff so they could understand the scope and timeline of the project, along with potential involvement expectations. I believe it was vital to include staff in the process since their participation would expand the reach of the project to as many clients as possible. Handouts were created and distributed along with guidance. Low and non-redeemers were individually contacted to assess barriers and troubleshoot issues. Store guided tours and purchasing trips were offered but never utilized. Following the intervention, the data was analyzed to assess the success of our intervention. Results were reported to local staff and offered to state-level contacts with the intention of reporting them at the next agency conference. Along with the outcome, local policy recommendations and future directions were shared.
Keywords: Women; Infant and children; WIC program; benefit utilization; nutrition education; food insecurity